Baby boomers engagement as traditional university students: benefits and costs. Issue 6 (2nd November 2017) - Hardy, Margaret; Oprescu, Florin; Millear, Prudence; Summers, Mathew
Abstract: This study draws from interviews of baby boomers (born between 1946 and 1965) enrolled in a traditional university programme. Interviews focussed on the mental, social and physical benefits of university education, exploring the aspirations of baby boomers as well as the social and academic barriers and costs they encountered. This qualitative phenomenological study investigated the perceptions, understandings and beliefs of 15 baby boomers from South-East Queensland who were returning to or commencing university level education. Informal semi-structured interviews were conducted and thematically analysed to provide a detailed account of the baby boomer students' university experience. Using an adapted health action process approach, with the health goal being replaced by a learning goal, the results confirm that university study in later life can be beneficial to the individual as well as to the wider community. This research can inform policy-making by emphasising the importance of lifelong learning and healthy ageing for the baby boomer generation. The results highlight the value of higher education creating a supportive environment for baby boomer students which, in addition to educational achievements, can assist participants in maintaining good health and making informed health care decisions in the future.